A higher preoperative total protein to albumin ratio independently predicted more severe postoperative acute kidney injury in patients with acute type A aortic dissection: a retrospective cohort study of 224 cases - Wang, Xiuhua; Xu, Hui; Tu, Guowei; Lai, Hao; Xu, Jiarui; Li, Xin; Luo, Zhe (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesIn this retrospective study, we investigated the incidence of postoperative acute kidney injury (AKI) and determined the predictors associated with AKI in patients underwent surgeries for acute type A aortic dissection (ATAAD).MethodsWe enrolled patients diagnosed with ATAAD and received operation. AKI was defined based on the Kidney Disease: Improving Global Outcomes criteria. Potential perioperative predictors were evaluated for postoperative AKI. Univariate and multivariate regression analyses were conducted to identify predictors associated with AKI following surgery. The primary end point was the incidence of postoperative AKI, while the secondary end points included in-hospital mortality and other major surgical complications.ResultsThis study enrolled 224 patients in all. There were 155 (69.2%) patients with postoperative AKI, including 55 (24.6%) with KDIGO stage 1, 45 (20.1%) with stage 2 and 55 (24.6%) with stage 3. Twenty-eight patients (12.5%) needed renal replacement therapy after surgery. The total in-hospital mortality was 2.7% (AKI vs. non-AKI: 3.2% vs. 1.4%, p = 0.669). Multivariate regression analysis found total protein concentrations [odds ratio (OR) 1.136, 95% confidence interval (CI): 1.032–1.250, p = 0.009], intraoperative blood loss (OR 1.002, 95% CI: 1.000–1.004, p = 0.042) and ventilation time (OR 1.011, 95% CI: 1.001–1.021, p = 0.026) were independently associated with AKI. The area under the receiver operating characteristic curve was 0.688 (95% CI: 0.617–0.759). Our predictive model demonstrated a sensitivity of 72.5% and a specificity of 57.4%. The ordinal logistic regression analysis found that age (OR 1.055, 95% CI: 1.027–1.084, p < 0.001), body mass index (OR 1.194, 95% CI: 1.104–1.291, p < 0.001), a high total protein to albumin ratio (OR 2.615, 95% CI: 1.234–5.540, p = 0.012) and ventilation time (OR 1.005, 95% CI: 1.001–1.008, p = 0.005) were independently associated with the severity of AKI.ConclusionA higher preoperative total protein to albumin ratio independently predicted more severe postoperative AKI in patients undergoing surgical treatment for ATAAD. Monitoring preoperative total protein concentrations and the total protein to albumin ratio may assist in identifying patients at higher risk of progressing to severe AKI, though further multicenter validation is required.